Environmental antibiotics drives the genetic functions of resistome dynamics. (February 2020) - Gao, Qun; Dong, Qiang; Wu, Linwei; Yang, Yunfeng; Hale, Lauren; Qin, Ziyan; Xie, Changyi; Zhang, Qiuting; Van Nostrand, Joy D.; Zhou, Jizhong
Highlights: Total antibiotic concentration decreased by factors of 10 to 1000 from manure and compost to soils. Abundances of virulence genes and antibiotic resistance genes were higher in manure than in soils. There were weak interconnections between ARGs and bacterial or fungal phylogeny. Microbial genes are good predictors for antibiotic concentration in the environment. Abstract: The increasing prevalence of antibiotic-resistant microorganisms imposes a global threat to public health. The over reliant use of antibiotics in the food industry has contributed considerably to the dissemination of antibiotics into various environments, yet the mechanisms by which antibiotic dissemination influences the assembly of the microbial community continues to remain obscure. Here, we examine bacterial and fungal community assemblies in swine manure, compost, compost amended, and unamended agricultural soil in five suburban areas of Beijing, China. Total antibiotic concentration decreased by factors of 10–1000 from manure and compost to soils. The bacterial α-diversity was found to be low in manure and compost samples, while the fungal α-diversity was similar across all samples. We detected significantly ( p < 0.05) higher relative abundances of well recognized pathogenic microbial taxa, virulence associated genes, and antibiotic resistance genes (ARGs) in manure and compost than those in agricultural soils, revealing the higher microbial capacity of pathogenicity, virulence and antibiotic resistance. Unexpectedly, the relative abundances of both bacterial and fungal taxa did not predict the antibiotic concentration. A possible explanation was that bacterial and fungal communities were mainly shaped by random assemblies. Rather, antibiotic concentration could be well predicted by relative abundances of antibiotic resistance, stress and virulence associated genes. Despite the weak interconnection between ARGs and the microbiome, we demonstrate that microbial genes should be the focal point in tracking the ecological effects of antibiotic dissemination by revealing microbial community patterns along the dissemination chain of antibiotics.